Comparative kinetics study on carbonation of ettringite and meta-ettringite based materials. (November 2020) - Chen, Bao; Horgnies, Matthieu; Huet, Bruno; Morin, Vincent; Johannes, Kévyn; Kuznik, Frédéric
Abstract: The use of ettringite-based materials for thermochemical heat energy storage has attracted researchers' attention in recent years since ettringite has advantages like low material cost and high energy storage density (~500 kWh/m 3 ). However, carbonation, which modifies its structure and reduces the capacity of energy storage, is an important hindrance to real applications. To address this issue, the present study focuses on the carbonation kinetics of three ettringite-based and corresponding meta-ettringite-based materials (dehydrated samples) exposed to different relative humidity (RH) and CO2 concentrations. A mixture of 80 wt% pre-blended Calcium Aluminate Cement/20 wt% OPC (C80P20) proved to be the most resistant against CO2 . The hydrated and dehydrated C80P20 grains carbonated slowly at 50% RH and 1 vol% CO2, consuming little ettringite after 28 days. At 90% RH, carbonation was accelerated such that all ettringite and meta-ettringite materials were depleted at 11 days with vaterite and aragonite as the main calcium carbonates. The produced CaSO4 hydrates were found as hemihydrate at 70% RH and gypsum at 90% RH. Finally, the thermal energy storage capacity (TESC) of the material was systematically quantified as essentially decreasing with the carbonation degree of ettringite-based materials.